IMPLEMENTATION OF CHEMO-ENTREPRENEURSHIP TEACHING APPROACH FOR IMPROVING STUDENTS' LIFE SKILLS - Nanik Wijayati; Wara Dyah Pita Rengga (Universitas Negeri Malang, 2016)
The Implementation of Chemo-entrepreneurship (CEP) Teaching Approach in Improving Students' Life Skills The study aimed at developing an innovative teaching method. Chemo-entrepreneurship (CEP) approach is a method is Chemistry teaching which relates the theory with everyday objects. This method provides the knowledge as well as the skills of Chemistry in order to transform raw materials into valuable products. The focus of the study was the improvement of students' achievement and the development of students' life skills. The subjects of the study were 39 students from the Chemistry Education Department of Universitas Negeri Semarang (UNNES). The data were obtained from the observation of the subjects, which were finally analyzed descriptively. The results of the study showed that the CEP teaching method was successfully implemented, and the students got better achievement. The study also revealed that the means of students' life skills were also improved.s' achievement of learning was increased. Students' average life skill score was also improved.